Cấu trúc địa chất tầng nông vùng đảo đá tây (Trường Sa) theo tài liệu địa chấn nông phân dải cao - Lương, Nguyễn Văn; Cương, Tống Duy (Vietnam Journal of Earth Sciences, 2003)
Geological structure of shallow strata in the Da Tay island region Truong Sa archipelago according to high resolution seismic profiling data